2017
DOI: 10.1519/jsc.0000000000001594
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrical Myostimulation on the Function of Lower Leg Muscles

Abstract: Electrical myostimulation (EMS) method is applied to improve skeletal muscle function. The aim of this study was to evaluate the efficacy of EMS applied to the sole and calf muscles on their strength and on maximal sprint performance. Each of 10 training sessions involved 10 seconds of stimulation and 50 seconds of rest for a total of 10 minutes. After the 10 training sessions, the maximal voluntary contraction (MVC) of right calf muscles increased by 6.0% from 830.0 ± 47.0 N to 878.0 ± 45.3 N (p ≤ 0.05). When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In recent years, EMS has begun to be popularly used in the fields of exercise and sports. There are many studies investigating the effect of EMS training on speed, vertical jump, strength, resistance, flexibility, aerobic and anaerobic capacities, neural adaptation, muscle activation and muscle functions [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, EMS has begun to be popularly used in the fields of exercise and sports. There are many studies investigating the effect of EMS training on speed, vertical jump, strength, resistance, flexibility, aerobic and anaerobic capacities, neural adaptation, muscle activation and muscle functions [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that EMS can significantly improve muscle functions in patients suffering from end-stage renal disease, chronic heart failure, chronic obstructive pulmonary disease and other severe conditions 19, 20, 21, 22, 23 . Furthermore, in trained athletes, EMS has shown effectiveness in enhancing the strength and function of the lower leg muscles 24 . There are also studies indicating that the regular EMS increase the oxidative capacity and enhance glucose disposal of the paralyzed muscles, to partly counteract the neurotrophic deficiency after the nerve injury 25, 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that ES training increased the strength of the lower limb muscles and improved their performance in healthy persons and athletes [6][7][8][9][10] , and it is considered to be effective for enhancing muscle function of the infraspinatus muscle. Previous studies have been conducted to estimate which parameters, e.g., intensity, frequency, and time are effective in increasing strength [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%